International Student Migration in Finland: The Role of Graduation on Staying - Mathies, Charles; Karhunen, Hannu (Journal of International Students, 2021)
There is increasing attention on the retention of international students with many stakeholders desiring to keep international students for long-term economic growth. This study examines the factors affecting international students to stay in Finland five years after initial enrolment with particular focus on the role graduation plays in students staying or leaving. Tracking 11 (years) entering cohorts for five years across national (Finland) data registries, we found evidence of an inverse relationship between graduation, degree type, and the probability of staying; higher the degree level of graduation, the decrease in probability an international student stays. We conclude that while graduation is a key metric and discussion point in national and institutional policy, our findings suggest focusing on improving international students’ ability to integrate into a host country’s labor market and promotion of an environment conducive for international students’ families, more than graduation, would produce higher stay rates of international students.